The Importance of the Training on Job Performance Dr. Mutwakil Abdellatif Elfadni - Mutwakil Abdellatif Elfadni (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2019)
Training has a very significant role in influencing the job performance, and in creating an effective performance which considered an investment factor on it. This paper aimed to find the importance of training on job performance and to provide suggestion as to how firm can improve its employee performance through effective training programs. The research approach adopted for the study conforms to qualitative research, as it reviews the literature and multiple case studies on the importance of training in enhancing the performance of the workforce. The study in hand faces the limitations as there are no adequate indications to correlate directly the relationship between training and employee performance. Hence, there is a need for conducting an empirical research in future to test the proposition discussed in the study. The study in hand provides brief overview of the literature about training effectiveness and how it contributes in enhancing the employee performance and ultimately concludes along with recommendation to give directions for future research by applying different level of analysis on exploring the impact of training practices on employee performance.